Negation Markers in Buginese - Arifuddin Balla; Ahmad Ardillah Rahman (English Language Education Department, Universitas Majalengka, 2023)
This study analyzed the expression of negation markers in Buginese. The study employed a descriptive qualitative method. The data for this study are some snippets of daily speech in Buginese Sinjai Dialect setting which we have verified as the native speakers. The results indicated that there are two main ways of expressing negation in Buginese which are negation marker dena' that can be used interchangeably with negation enna'. Negation dena'/enna' is used if the predicate is verbal, adjectival, or with prepositions. Another negation is tannia which is used in relative clause. Negation tannia is used if the predicate is nominal either object or subject. This study can contribute to provide references in Buginese negation as there are a few references in this specific topic.